RESPONSE OF SOME WHEAT GROWTH TRAITS FOR FOR FOLIAR SPRAYING WITH HUMIC AND GLUTAMIC ACID - & Zeboon, Baqir (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
A field experiment was conducted at the Agricultural Experiment Unit, College of Agriculture Engineering Sciences, University of Baghdad, during two winter seasons 2016-2017 and 2017-2018 to study the response of some growth traits for wheat Cv. Al forat to foliar spraying using with humic glutamic acid and acid. A factorial experiment was with in Randomized Complete Block Design applied three replications, it involved two factor ,first factor was glutamic acid with three concentrations (0,250,500) mg L-1, second factor was humic acid with three concentrations (0,1,2) ml L-1, have been sprayed at tillering and flowering stages. The results showed that all the studed growth traits (plant height, ,number of tillers, flag leaf area dry weight for plant , crop growth rate ,relative growth rate and biological yield) were affected  by spraying with humic acid and glutamic acid for two season concentration , 2ml -1 from humic acid was superior on most of studies traits , as for glutamic acid ,plants treated with concentrations 250 and 500 mg L-1 were produced the highest mean for studies traits but without significant difference between them in some traits .The interaction between two factors was significant on most studies growth traits .